OpenCL-accelerated first-principles calculations of all-electron quantum perturbations on HPC resources - Wu, Zhikun; Shang, Honghui; Wu, Yangjun; Zhang, Zhongcheng; Liu, Ying; Zhang, Yuyang; Ouyang, Yucheng; Cui, Huimin; Feng, Xiaobing (Frontiers in Chemistry, 2023)
We have proposed, for the first time, an OpenCL implementation for the all-electron density-functional perturbation theory (DFPT) calculations in FHI-aims, which can effectively compute all its time-consuming simulation stages, i.e., the real-space integration of the response density, the Poisson solver for the calculation of the electrostatic potential, and the response Hamiltonian matrix, by utilizing various heterogeneous accelerators. Furthermore, to fully exploit the massively parallel computing capabilities, we have performed a series of general-purpose graphics processing unit (GPGPU)-targeted optimizations that significantly improved the execution efficiency by reducing register requirements, branch divergence, and memory transactions. Evaluations on the Sugon supercomputer have shown that notable speedups can be achieved across various materials.